Pengaruh Accounting Disruption Pada Kualitas Audit Dimediasi Beban Kerja Audit : (Studi pada Kantor Akuntan Publik di Kota Malang) - Seviana, Via; Adam, Helmy (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aims to prove the effect of accounting disruption on audit quality with audit workload as an intervening variable at the Public Accounting Firm in Malang City. This research method uses quantitative research methods. This study uses primary data with data collection techniques through distributing questionnaires to 56 research samples using the convenience sampling method . The results of this study indicate that accounting disruption has a positive effect on audit quality directly and has a negative effect on audit workload. Audit workload has a negative effect on audit quality and there is an effect of accounting disruption on audit quality through mediation of audit workload. Changes in information technology in the field of corporate accounting make it easier for auditors to track audit evidence so as to improve audit quality.